Post mortem interval calculation of oryctolagus cuniculus through forensic entomofauna – a tool for resolving medicolegal issues in crime scenes - Attaullah, Mohammad; Ullah, Fahim; Khan, Imran; Ilahi, Ikram; Zahoor, Muhammad; Amin, Muhammad; Ullah, Riaz; Ali, Essam A.; Jan, Arif; Bibi, Sidra (Penerbit Universiti Kebangsaan Malaysia, 2024)
Post mortem interval (PMI) is an essential tool in crime scene investigations and is pivotal for resolving medicolegal issues. Developmental rates of insects can be utilized for the calculation of PMI of known and unknown animal and human cadavers. In the present study, PMI for rabbit, Oryctolagus cuniculus (Linnaeus 1758) was calculated through insect developmental rates and insect successional patterns on decomposing carcass of O. cuniculus. A total of 8 species of insects belonging to three orders and 8 families were identified on the O. cuniculus carcass. The blow fly, Chrysomya albiceps (Wiedemann 1819) belonging to the family Calliphoridae was the common and first visitor species to the rabbit carcass. The developmental rate of C. albiceps associated with the ambient climatic conditions was used as a model for the calculation of PMI. Temperature correction factor of the carcass temperature versus met station temperature was found as y = 0.9185x + 3.3624; R² = 0.8343. The accumulated degree days (∑ADD) were found as 535 while the accumulated degree hours (ADH) were found as 12842 with a resultant PMI of 7 days (ADD) and 167.4 h (ADH). Five decomposition stages of O. cuniculus were identified as fresh, bloated, active decay, advanced decay and dry remains stage. Findings of the present study can be applied for the calculation of PMI of known and unknown animal and human cadavers for resolving medicolegal issues in crime scenes.